Transcatheter Mitral Valve Replacement: Current Evidence and Concepts. Issue 1 (2021) - Demir, Ozan M; Bolland, Mhairi; Curio, Jonathan; Søndergaard, Lars; Rodés-Cabau, Josep; Redwood, Simon; Prendergast, Bernard; Colombo, Antonio; Chau, Mei; Latib, Azeem
No abstract available